Effects of the environment on the uracil molecule ionization induced by 12C4+ ion beam. (July 2015) - Markush, P; Bolognesi, P; Cartoni, A; Rousseau, P; Maclot, S; Delaunay, R; Domaracka, A; Kocisek, J; Castrovilli, M; Huber, B A; Avaldi, L
Synopsis: In this study the fragmentation of isolated uracil molecules, uracil clusters and hydrated uracil clusters induced by 12 C 4+ ions at 36 keV energy has been investigated. The mass spectra obtained by a TOF mass spectrometer are analyzed and compared to each other in order to see how the environment affects the fragmentation dynamics. The main differences between the mass spectra are highlighted and possible fragmentation pathways are proposed.